2018
DOI: 10.22159/ajpcr.2018.v11i9.26747
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance Study of Antiretroviral Therapy in Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome Patients at Antiretroviral Therapy Centre, Jabalpur

Abstract: Objective: The objective of the study was to assess the adverse drug reactions (ADRs) of antiretroviral therapy along with its causality, severity, and preventability.Method: A prospective as well as a retrospective observational study with a sample size of 260, jointly conducted in the Department of Pharmacology and antiretroviral therapy (ART) center of N.S.C.B. Medical College Jabalpur, India, from March 2016 to July 2017. We observed various ADRs to ART in human immunodeficiency virus (HIV)/acquired immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is in correlation with the study conducted by Parmar because they found that HIV infected patients taking Efavirenz based HAART (TLE) had better clinical outcomes, higher survival rate, and increase in CD4 cell count after the HAART (p=0.001) compared to those taking Nevirapine based HAART (ZLN) 11 . In addition to efficacy, ADR's were found to be predominant with NVP based therapy 12 . However, a study conducted by Bhuvana and Hema shows that ZLN is the most commonly prescribed regimen which is not by this study 13 .…”
Section: Statistical Analysis and Interpretationmentioning
confidence: 99%
“…This is in correlation with the study conducted by Parmar because they found that HIV infected patients taking Efavirenz based HAART (TLE) had better clinical outcomes, higher survival rate, and increase in CD4 cell count after the HAART (p=0.001) compared to those taking Nevirapine based HAART (ZLN) 11 . In addition to efficacy, ADR's were found to be predominant with NVP based therapy 12 . However, a study conducted by Bhuvana and Hema shows that ZLN is the most commonly prescribed regimen which is not by this study 13 .…”
Section: Statistical Analysis and Interpretationmentioning
confidence: 99%